Experimental Study on Mechanical Properties of CFRP-Confined Concrete Columns under Continuous Semi-Submergence of Sulfate - Mingxi Cai; Lijun Shao; Jiawei Zhang; Kaijin Xu; Jie Zhang; Penggang Li (Advances in Civil Engineering)
To investigate the mechanical properties of carbon-fiber-reinforced-polymer (CFRP)-restrained concrete in a saline soil environment, the degradation of the mechanical properties of CFRP-restrained concrete columns under the effect of continuous sulfate semisoak erosion is investigated based on sulfate continuous semisoak erosion, and unrestrained concrete columns with the same specifications are used in comparison tests. The results show that the strength, stiffness, and ductility of both plain concrete columns and CFRP-confined concrete columns first increase and then decrease after the continuous semi-submersion erosion by sulfate; compared with plain concrete columns, the decline rates of strength and stiffness of CFRP-confined concrete columns are significantly lower, and the CFRP demonstrates a certain protective effect on the core concrete. Through a regression analysis of experimental data, strength and ultimate strain models of CFRP-confined concrete columns under the continuous semi-submergence of sulfate are proposed based on the existing ultimate strength and ultimate strain models of CFRP-confined ordinary concrete columns, and a stress–strain model of CFRP-confined concrete columns under the continuous semi-submergence of sulfate is established. Based on a comparison with experimental data, the model prediction curves indicate good agreement with the experimental curves and can therefore provide a theoretical basis and practical reference for CFRP-reinforced semi-submerged concrete in saline soil areas.